Correlation of Fine Needle Aspiration Cytology and Histopathology of the Neck Swellings Presenting at National Academy of Medical Sciences, Kathmandu, Nepal - Devkota, Harihar; Sibakoti, YC; Menyangbo, S; Basnet, S; Jha, MK; Banstola, L (Birat Journal of Health Sciences, 2017)
Introduction Neck masses are frequently found in clinical practice. A spectrum of pathological lesions ranging from inflammation to benign and highly malignant manifestation is observed. Fine needle aspiration cytology (FNAC) of neck masses is a quick, easy, safe and cheap technique in the diagnosis which has been a well-accepted procedure in diagnosing various swellings. Histopathology is a gold standard technique in diagnosing any swelling which also provide detail architecture, however it also requires OT setings, more manpower, expensive, time consuming, more traumatic and can sometimes become difficult. Objective The objective of our study was to evaluate the frequencies of neck swellings and how efficacy FNAC is in diagnosing neck masses by correlating the gold standard histopathological examination. Methodology A Hospital based descriptive cross sectional prospective study was conducted in 50 patients with neck swellings presenting in the surgery OPD and admitied patient for some other reasons. FNAC and histopathological examinations were done from those lesions and were compared. The sensitivity, specificity and accuracy rates were calculated. Data entry and analysis was performed using SPSS. Results A total of 50 patient were subjected to both FNAC and histopathology examination (HPE). Out of 50 cases, 25 were male and 25 were female. The age ranged from 16 to 82 years. Lymph nodes 22 (44%) was the most common case, followed by thyroid 17 (34%), salivary glands 10 (20%) and soft issue 1 (2%).Among all Tubercular lymphadenitis (18%) followed by papillary carcinoma of thyroid (14%),metastatic carcinoma of lymph node, NHL, and pleomorphic adenoma 10% each. The sensitivity of FNAC in diagnosing neck masses is 90.08%, specificity is of 98.53%, and diagnostic accuracy is of 87.64%. Conclusion FNAC is a simple, fast, inexpensive, and minimally invasive technique which can be used as the first line investigation in diagnosing neck swellings. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, page: 206-210